Improving saltland revegetation through understanding the “recruitment niche”: potential lessons for ecological restoration in extreme environments - Barrett-lennard, Edward; Norman, H.; Dixon, Kingsley (Blackwell Science Inc., 2016)
Germination and emergence are often the most precarious stage in a plant’s lifecycle: plants are particularly vulnerable to environmental stress at this time. Despite these constraints, plants colonize much of the planet including extreme environments. We argue that for many species, establishment in extreme situations is not because seed is adapted to germinate in extreme environments but because it falls into, and is spatially and temporally nurtured within, more benign “recruitment niches.” This principle has importance for revegetation in extreme environments such as the world’s drylands. Using examples from ground-breaking experiments conducted by CV Malcolm and colleagues between 1976 and 1982 on saltland revegetation with halophytes, we show that recruitment niches can be constructed based on an understanding of the key requirements that seeds need in their immediate environment to establish. As part of their studies, Malcolm’s team developed a “niche seeder” capable of distributing and precisely placing fruits of Atriplex species in an elevated “V”-shaped mound (to decrease waterlogging), covering the fruits with vermiculite (to decrease capillarity and therefore salinity at the soil surface), and spraying the placements with black paint (to increase soil temperatures).Subsequent studies in arid environments showed that the establishment of woody plants was also improved using stones on the soil surface to develop appropriate recruitment niches. Malcolm's identification of the “recruitment niche” is an important principle of broader relevance to the revegetation of degraded landscapes in extreme environments. In addition, the development of the niche seeder is an important case study in ecological restoration.